COF membranes with uniform and exchangeable facilitated transport carriers for efficient carbon capture. Issue 21 (17th May 2021) - Yang, Leixin; Yang, Hao; Wu, Hong; Zhang, Leilang; Ma, Hanze; Liu, Yutao; Wu, Yingzhen; Ren, Yanxiong; Wu, Xingyu; Jiang, Zhongyi
Abstract : Ultrathin and defect-free COF membranes with uniform and exchangeable facilitated transport carriers were fabricated for efficient carbon capture. Abstract : Facilitated transport membranes, with a uniform distribution of facilitated transport carriers, are highly desirable to reduce the separation energy barrier. Nevertheless, the disordered and random assembly of membrane building materials/blocks makes it hard to obtain the controlled uniform distribution of carriers within membranes. Covalent organic frameworks (COFs), equipped with a regular structure and tailored functionality, provide a favorable platform for the uniform distribution of carriers. Herein, we report an ion-exchange strategy to achieve a uniform distribution of facilitated transport carriers within a cationic COF membrane for efficient carbon capture. With the assistance of a small amount of flexible graphene oxide (GO), the potential defects between the junctions of cationic COF nanosheets were eliminated, and ultrathin (20–60 nm), defect-free COF membranes were obtained. By synergistically intensifying the diffusion selective and facilitated transport mechanisms within membranes, the optimized COF membrane exhibits a CO2 permeance of 164.2 GPU with a CO2 /CH4 selectivity of 27, both of which exceed those of pure COF membranes in most literature studies. Our findings may stimulate further research on functionalized COF membranes and other kinds of organic framework membranes with uniformly distributed carriers for molecule separation.